Design and Implementation of Agricultural Spraying Drone - Bibhuti Rath; P. Guruvulu Naidu; B. Ravikumar (International Journal of Robotics and Automation in Mechanics, 2023)
In this brief an attempt has been made to develop an agricultural drone to spray pesticides in an agricultural farm. In India, agriculture is one of the key economic sectors. Crop production rates are influenced by factors such as temperature, moisture content, rainfall, etc. The field of husbandry is also influenced by other elements, such as pests, complaints, diseases, etc., which can be managed by giving crops the right care. Fungicides may increase crop production, but they may also have an effect on people's health. Now-a-days to reduce the burden on the growers, remote controlled drones should be used to spot fungicides and germicides. This design deals with design and development of a drone to spray fungicides and germicides to kill the pests and insects to boost the crop of crop in our land. In this work, we developed the hexa-copter agricultural drone sprayer. Pesticides up to 0.5 liters in volume can be carried by the drone. A pesticide spraying tool is part of the drone, and the ground control station uses a remote control to operate it. Pesticides can be released from the spraying equipment at a rate of 0.0166 liters per second. The drone can fly for about 8 minutes. The planned drone will lessen the amount of labour needed and the amount of time needed to spray pesticides as well as the health risks to the farmers.
Keywords: BLDC Motor; Hexa–copter drone; esc; spraying system